2010
DOI: 10.1289/ehp.0901559
|View full text |Cite
|
Sign up to set email alerts
|

No Association between Arsenic Exposure from Drinking Water and Diabetes Mellitus: A Cross-Sectional Study in Bangladesh

Abstract: Background The long-term effects of arsenic exposure from drinking water at levels < 300 μg/L and the risk of diabetes mellitus remains a controversial topic. Method We conducted a population-based cross-sectional study using baseline data from 11,319 participants in the Health Effects of Arsenic Longitudinal Study in Araihazar, Bangladesh, to evaluate the associations of well water arsenic and total urinary arsenic concentration and the prevalence of diabetes mellitus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
3
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 56 publications
3
77
3
2
Order By: Relevance
“…26 However, a study conducted in Bangladesh did not show any association between diabetes and arsenic when the concentration of arsenic was less than 300 ppb in water. 27 In the current study significant association could not be found between the lower dose of arsenic exposure and DM and IGT amongst the arsenic exposed young adults.…”
Section: Discussioncontrasting
confidence: 69%
“…26 However, a study conducted in Bangladesh did not show any association between diabetes and arsenic when the concentration of arsenic was less than 300 ppb in water. 27 In the current study significant association could not be found between the lower dose of arsenic exposure and DM and IGT amongst the arsenic exposed young adults.…”
Section: Discussioncontrasting
confidence: 69%
“…On the contrary to these studies, the Health Effects of Arsenic Longitudinal Study in Bangladesh found no association between arsenic levels in water and urine samples and type 2 diabetes (Chen et al, 2010). Similarly, a reanalysis of the data from the 2003-2004 National Health and Nutrition Examination Survey in the USA did not indicate that arsenic exposure would increase the risk of diabetes (Steinmaus et al, 2009).…”
Section: Populationmentioning
confidence: 84%
“…Some studies also suggested the relationship 35 http://www.ijt.ir; Volume 11, No 6, November-December2017 between arsenic exposure and prevalence of diabetes [13,19]. The relationship also has suggested in studies conducted in industrial exposure of arsenic [20][21][22].…”
Section: Discussionmentioning
confidence: 96%